STEREOTIPIA DE GEN - O PROBLEMĂ PSIHOSOCIALĂ - USM ADMIN (Moldova State University, 2012)
Society in which we live, consisting of "cells" predominantly patriarchal, gender stereotypes is dominated by that means that men are by nature are more rational and autonomous, so they can be actors of the public sphere, while women have limited autonomy, are more emotional and more about nature, family, private sphere. Gender stereotypes show general social vision to people's behavior, gender, outside etc. Gender stereotypes do not respect people's individual characteristics, but force them to do poorly their real desires. They influence behavior, relationships between men and women before and after marriage, etc. Sometimes stereotypes are harmful because it causes inappropriate behavior, give rise to - discrimination.